Citizens’ Perspective on the Effect of Court Sentencing and Preferred Crime Reduction Strategies in Mthatha Judicial Area, South Africa - Emeka E. Obioha; Anga Dlakulu; Ishmael Mugari (E-Journal of Humanities, Arts and Social Sciences, 2023)
This study explored the citizens’ perspectives on the potency of court sentencing on crime control in the Mthatha policing area of South Africa. It gathered citizens’ views on effective crime reduction strategies. The study comes against a background of an upsurge in crime within South Africa and in the Mthatha policing precinct, in particular. A survey was used to gather data on a sample of 90 purposefully sampled residents of the Mthatha area. The fact that offenders get a chance to renew their lives while they are in prison topped the list of effects of court sentencing, followed by the finding that when criminals are sentenced, their criminal behaviour gets worse. The preventive and deterrent effect of court sentencing was also confirmed in this study. As regards crime prevention, respondents mainly favoured primary and secondary crime prevention techniques, which are more proactive, as shown by the majority’s support of early childhood interventions. Early childhood positive socialisation is therefore recommended as the key sustainable mechanism for the future prevention of criminal behaviour in South African society on a long-term basis.